Vegetation Response to Grazing Management in a Mediterranean Herbaceous Community: A Functional Group Approach - Sternberg, Marcelo; Gutman, Mario; Perevolotsky, Avi; Ungar, Eugene D.; Kigel, Jaime (The Journal of applied ecology, 2000)
1. A 4-year study was conducted in a Mediterranean herbaceous community in north-eastern Israel to investigate the effects of cattle grazing management on the structure and composition of the community. Understanding the effects of grazing on the dynamics of Mediterranean herbaceous communities is important in formulating rational management plans for both conservation and sustainable animal production. 2. The relationships among plant functional groups were studied in the context of inter-annual variation in rainfall. Treatments included manipulations of stocking rates (moderate, heavy and very heavy) and grazing regimes (continuous vs. seasonal), in a factorial design. 3. The herbaceous community was rich in species, with 166 species recorded at the site, of which 74% were annuals. Plant cover was dominated by 10 species that accounted for 75% of the total cover. 4. Inter-seasonal rainfall variation was a dominant factor in the expression of different grazing treatments on the structure of the plant community. Grazing effects were stronger in wet years than in dry years. 5. Paddocks under continuous grazing were higher in number of species compared with paddocks subjected to seasonal grazing, independently of grazing intensity. 6. Functional group analyses showed that reduction in cover of tall grasses was correlated with an increase in cover of prostrate annual legumes and less palatable groups such as annual and perennial thistles, crucifers and forbs. 7. Cover of functional groups composed of hemicryptophytic species was less variable (lower coefficient of variation) in response to grazing treatments and interannual variation in climatic conditions compared with functional groups with annual species. 8. The persistence of the dominant species and the relatively small amplitude of change in plant cover of the functional groups suggest that the community was rather stable in spite of wide variation in grazing regimes and climatic conditions. East-Mediterranean grasslands appear to be adapted to grazing due to their long history of human association.